Metadata Repositories in Database-driven Information Systems. (2015) - Muji, Marius
Abstract: Database-driven information systems provide, by definition, a good level of integration for the various data representations corresponding to heterogeneous information requirements, generated by users with different business perspectives. However, current technologies provide little support for the integration of the system specifications. This paper identifies the key factors which contribute to the semantic integration of the information system metadata, and proposes a possible architecture for an integrated metadata repository.